Wormhole Detection Based on Ordinal MDS Using RTT in Wireless Sensor Network. (7th November 2016) - Mukherjee, Saswati; Chattopadhyay, Matangini; Chattopadhyay, Samiran; Kar, Pragma
Abstract : In wireless communication, wormhole attack is a crucial threat that deteriorates the normal functionality of the network. Invasion of wormholes destroys the network topology completely. However, most of the existing solutions require special hardware or synchronized clock or long processing time to defend against long path wormhole attacks. In this work, we propose a wormhole detection method using range-based topology comparison that exploits the local neighbourhood subgraph. The Round Trip Time (RTT) for each node pair is gathered to generate neighbour information. Then, the network is reconstructed by ordinal Multidimensional Scaling (MDS) followed by a suspicion phase that enlists the suspected wormholes based on the spatial reconstruction. Iterative computation of MDS helps to visualize the topology changes and can localize the potential wormholes. Finally, a verification phase is used to remove falsely accused nodes and identify real adversaries. The novelty of our algorithm is that it can detect both short path and long path wormhole links. Extensive simulations are executed to demonstrate the efficacy of our approach compared to existing ones.